Penguatan Kemitraan Lintas Iman Muslim dan Bahai melalui Bincang Diskursus Keragaman (BIDUK) #01 ISAIS UIN Sultan Syarif Kasim Riau - Muhammad Ansor; Laila Sari Masyhur; Bambang Hermanto; Mhmd. Habibi (Asskruie: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article discusses the implementation of interfaith partnership strengthening activities between Muslims and Baha'is in Riau through the organization of the Diversity Discourse Chat (BIDUK) #01 by ISAIS UIN Sultan Syarif Kasim Riau. This activity argues that interfaith partnerships in resolving religious relationship issues can be conducted not only through formal approaches facilitated by the state but also through both informal and formal encounters of each community and the willingness to discuss problems related to religious relationships, including sensitive topics. In this regard, ISAIS UIN Sultan Syarif Kasim Riau facilitates periodic discussions packaged through the BIDUK program, which addresses issues of diversity governance in Indonesia. The BIDUK #01 discussion was held as an effort to strengthen mutual understanding between Bahá'ís and Muslims in Riau in addressing issues related to the religious relations of both communities. In the end, the BIDUK discussion contributed to broadening the horizons of each community's members, showing that differences in religious beliefs do not hinder the partnership between Muslims and Bahá'ís in Riau in addressing national issues related to religious relations in Indonesia.